2015
DOI: 10.1016/j.mce.2014.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transmembrane domains that regulate spatial arrangements and activity of prokineticin receptor 2 dimers

Abstract: The chemokine prokineticin 2 (PK2) activates its cognate G protein-coupled receptor (GPCR) PKR2 to elicit various downstream signaling pathways involved in diverse biological processes. Many GPCRs undergo dimerization that can modulate a number of functions including membrane delivery and signal transduction. The aim of this study was to elucidate the interface of PKR2 protomers within dimers by analyzing the ability of PKR2 transmembrane (TM) deletion mutants to associate with wild type (WT) PKR2 in yeast usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…However, as Ca 2+ flux curves of the co-transfected cells paralleled that of the wild-type-transfected cells, enhanced signal transduction rather than delayed desensitization appears to be the major effect of p.C242fsX305. These results are consistent with those of a previous study by Sposini et al [12]. Our p.C242fsX305 mutant may modify the spatial arrangement of PROKR2 protomers to form hyperactive heterodimers, as in the case of the TM1-5 variant [12].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…However, as Ca 2+ flux curves of the co-transfected cells paralleled that of the wild-type-transfected cells, enhanced signal transduction rather than delayed desensitization appears to be the major effect of p.C242fsX305. These results are consistent with those of a previous study by Sposini et al [12]. Our p.C242fsX305 mutant may modify the spatial arrangement of PROKR2 protomers to form hyperactive heterodimers, as in the case of the TM1-5 variant [12].…”
Section: Discussionsupporting
confidence: 94%
“…. Our p.C242fsX305 mutant may modify the spatial arrangement of PROKR2 protomers to form hyperactive heterodimers, as in the case of the TM1‐5 variant .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PROKR2 variants have been further described in patients with idiopathic combined pituitary hormone deficits (CPHD) including gonadotropin deficiency (Raivio et al 2012, Reynaud et al 2012. The PROKR2 also forms constitutive homomers in vivo ( Marsango et al 2011), and specific protomer-protomer interfaces for the oligomer have been suggested ( Sposini et al 2015). Future investigation of the relationship between oligomerization and pathogenic biased signaling modulation at this receptor is of interest.…”
Section: R68 Reviewmentioning
confidence: 99%